PENGARUH AKTIVA PAJAK TANGGUHAN, KEPEMILIKAN MANAJERIAL DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA DENGAN BEBAN PAJAK TANGGUHAN SEBAGAI VARIABEL PEMODERASI: Studi Empiris Pada Perusahaan Sektor Barang Konsumsi Primer Yang Terdaftar Di BEI - Samjaya, Asipah; Djohar, Chaidir (LPPM Universitas Bina Bangsa, 2023)
The purpose of this research is to examines and analyses the effect of deferred tax assets, managerial ownership, and company size on earnings management with deferred tax expense as a moderating variable. This research uses quantitative methods. The population used in this study consists of 87 companies in the primary consumption sector which are listed on the Indonesia Stock Exchange. The number of samples in this company consists of 10 companies obtained by purposive sampling method based on predetermined criteria. Data processing uses a statistical tool in the form of the EViews 10 program by conducting panel data regression analysis. The results of this study indicate that (1) deferred tax assets affect earnings management. (2) Managerial ownership has no effect on earnings management. (3) Company size has no effect on earnings management. (4) Deferred tax assets, managerial ownership and firm size simultaneously affect earnings management. (5) Deferred tax expense can moderate the effect of deferred tax assets on earnings management. (6) Deferred tax expense is unable to moderate the effect of managerial ownership on earnings management. (7) Deferred tax expense is unable to moderate the effect of company size on earnings management